Facile synthesis of MoO3/rGO nanocomposite as anode materials for high performance lithium-ion battery applications - Naresh N.; Jena P.; Satyanarayana N. (My University, 2025)
Pristine molybdenum trioxide with reduced graphene oxide (rGO) composite (MoO3/rGO) was prepared via facile high-energy ball-milling process followed by ultrasonication method. The structure and morphology of the prepared MoO3 nanoparticles and MoO3/rGO composites were investigated using XRD, Raman, FE-SEM and HR-TEM images. XRD results confirm the formation of pure orthorhombic structured α-MoO3 phase without any presence of impurities. FE-SEM and HR-TEM images shows the formations of rod shape MoO3 nanoparticles with particle size approximately 100–200 nm in diameter and 1 μm length. Raman spectroscopy analysis further confirms the formation of phase pure MoO3/rGO composite. The electrochemical analysis of MoO3/rGO composite exhibits an outstanding specific capacity of 568 mA h g−1 even after 100th cycle with an coulombic efficiency more than 90% at a higher current density of 500 mA g−1, which is much higher than commercially used graphite and reported literature on MoO3 as anode materials for lithium-ion battery applications. MoO3/rGO composite exhibits excellent rate performance, even at higher current density 1000 mA g−1, the observed capacity is found to be 502 mA h g−1. When the current density switched from 1000 mA g−1 to 100 mA g−1 there is an enhancement in the capacity up to 853 mA h g−1. The observed excellent electrochemical properties of MoO3/rGO composites prepared via facile high-energy ball-milling process followed by ultrasonication method was explained in detail on the basis of phase purity, small particle size, high surface area, and improved conductivity. © 2019